Extending timed automata for compositional modeling healthy timed systems - Braberman, V. (2002)
We introduce the notion of Timed I/O Components as Timed Automata "á la" Alur & Dill where an "admissible" I/O interface is declared. That notion has, what we consider, a key modeling property: non-zeno preservation under syntactically-checkable "I/O compatibility" among interacting components. Also a reduced parallel composition is posssible based on the ability of statically detect influence of behavior between components [8,10,11]. On the other hand, with some simple extra conditions, modular assume-guarantee style of reasoning like [15,19] is valid in our model. © 2002 Published by Elsevier Science B. V.